Transaction costs in public-private partnerships: a first look at the evidence - Gerti Dudkin; Timo Välilä (European Investment Bank (EIB), 2005)
This paper presents the results of one of the first systematic analyses of the magnitude and determinants of transaction costs in public-private partnerships (PPPs). Given limited data availability, the analysis is confined to procurement-phase costs of bidding and contract negotiation, thus excluding costs related to contract monitoring and renegotiation in the operational phase. Notably, no attempt is made to compare transaction costs in PPPs to those in traditional public procurement of investment projects, nor to compare them to cost savings achieved through PPPs. Even so, some interesting results emerge. As regards the level of transaction costs in the procurement phase, it is estimated that the total costs amount on average to well over 10 percent of the capital value of the project. Transaction costs to the public sector and the winning bidder vary between countries (legal systems) and sectors, and they are significantly higher in small projects (below 25 million) and in projects that take long (over 50 months) to procure. In contrast, neither experience in setting up partnerships nor the number of bidders affect the costs to the public sector and the winning bidder.
Keywords: H54; L33; C14; 330